Brief Research Report: Estimation of the Protein Digestibility-Corrected Amino Acid Score of Defatted Walnuts - Lackey, Kimberly A.; Fleming, Stephen A. (Frontiers in Nutrition, 2021)
Introduction: Walnuts are considered a good source of essential fatty acids, which is unique among the tree nuts. Walnuts are also composed of about 10-15% protein, but the quality of this protein has not been evaluated. Pistachios and almonds have been evaluated for their protein content using a protein digestibility corrected amino acid score (PDCAAS), but it is unclear how the quality of protein in walnuts relates to that in other commonly-consumed tree nuts. The objective of this study was to substantiate the protein quality of walnuts by determining their PDCAAS. Methods: A small, 10 day dietary intervention trial was conducted using male Sprague-Dawley rats (n = 8, 4 per group) with two arms: a nitrogen-free diet and a diet containing protein exclusively from defatted walnuts. Feed intake and fecal output of nitrogen were measured to estimate true protein digestibility and the amino acid composition of walnuts compared to child and adult populations were used to calculate amino acid scores and PDCAAS. Results: The true protein digestibility score of raw walnuts was calculated to be 86.22%. Raw walnuts contained 15.6 g protein/ g walnut with amino acid scores of 0.45 and 0.63 for children ages 6 months to 3 yr and 3-10 yr, respectively. For each population, a PDCAAS of 39% and 46% were calculated, respectively. Conclusions: This is the first known assessment of the PDCAAS of walnuts. Like almonds, they appear to have a low-to moderate score, indicating they are not a good source of complete protein.